Revolutionizing Naval Defense Operations: Enhancing Autonomy and Capabilities of Unmanned Surface Vessels (USV) Through Advanced Technologies - Sophia, Sally; Azizan, Akmal; Zahra, Salma (The Republic of Indonesia Defense University, 2024)
The rapid integration of autonomous systems into military operations has revolutionized naval defense, with Unmanned Surface Vessels (USVs) emerging as a critical technology for maritime operations. USVs offer unique advantages in surveillance, reconnaissance, and maritime security. However, their effectiveness remains constrained by the reliance on human operators for critical decision-making, particularly in complex and rapidly evolving maritime environments. This study addresses these limitations by advancing USV autonomy through the integration of artificial intelligence (AI), resilient communication networks, and multisensory navigation systems. Through a comprehensive literature review, this research evaluates current USV applications, identifies gaps in existing technologies, and explores advancements in other countries, including case studies of operational successes and failures. A comparative analysis of Unmanned Aerial Vessels (UAVs) and Unmanned Underwater Vehicles (UUVs) is also conducted to highlight the unique role of USVs in naval operations and justify their selection for this study. The findings reveal that AI-driven decision-making reduces human oversight, enhances adaptability, and increases operational efficiency. Resilient communication protocols ensure coherent operations in contested environments, while multisensory navigation systems improve situational awareness and environmental responsiveness. These innovations collectively enhance mission success rates and tactical flexibility, underscoring the transformative potential of autonomous USVs in modern naval defense. The study concludes with a robust framework for advancing USV technologies, advocating their integration into naval operations to address the complexities of contemporary maritime threats and redefine the future of autonomous maritime systems.